Pulmonary expression of MYCN mRNA following exposure to 2,4-D with or without endotoxin challenge - GEETIKA, GEETIKA; SODHI, S S; MUKHOPADHYAY, C S; RAMNEEK, RAMNEEK; SETHI, R S (The Indian Journal of Animal Sciences, 2019)
The present study aimed to observe the expression of MYCN in lungs of mice following chronic exposure of 2,4-D with or without lipopolysaccharide (LPS). 2,4-D was administered orally dissolved in corn oil at high and low dose (1/10th and 1/20th of LD50) for 90 days. After 90 days of exposure, animals from each group were challenged with LPS/normal saline solution at 80 μg/animal. The lung tissues were processed for microarray and real time studies. LPS resulted decrease (–0.173 fold) in m-RNA expression level of MYCN as compared to control, while High dose of 2,4-D alone and in combination with LPS resulted 0.949-fold change and 1.656-fold change increase in expression of MYCN m-RNA, respectively, as compared to control. Similarly, Low dose of 2,4-D alone or in combination with LPS also altered MYCN expression. The microarray data when validated by Real Time PCR was found to be in concordance with the Real Time PCR data. The data taken together suggest that, high and low exposure of 2,4-D alone or in combination with LPS alters expression of MYCN at m-RNA level.